Molecular Sieves Mediated Green Per-O-Acetylation of Carbohydrate Templates and Lipase Catalyzed Regioselective Alcoholysis of 2,3,5-Tri-O-Acetyl-D-Ribonolactone - Cardozo,Herbert M.; Ribeiro,Thaís F.; Sá,Marcus M.; Sebrão,Damianni; Nascimento,Maria G.; Silveira,Gustavo P. (Sociedade Brasileira de Química, 2015)
The per-O-acetylation of D-ribono-1,4-lactone and representative carbohydrates through the combination of acetic anhydride and molecular sieves under solvent-free conditions is demonstrated. The use of 13X/KCl molecular sieves as the heterogeneous catalyst was found to be more efficient than the excess of pyridine normally employed in the conventional method, giving high yields of the expected peracetylated product after 3 h at 25 ºC or 1 h at 50 ºC. The transformation can be carried out in gram scale and in an open flask. Additionally, the catalyst is readily separated from the reaction medium and can be reutilized without significant loss of activity. This green procedure for acetylation was extended to D-ribonolactone derivatives and natural carbohydrates. To demonstrate the synthetic utility of the method, 2,3,5-tri-O-acetyl-D-ribonolactone was selected as the substrate for the regioselective alcoholysis of acetyl group catalyzed by Candida antarctica lipase B in EtOH to selectively produce 2,3-di-O-acetyl-D-ribonolactone in gram scale.